Mapping Value Co-Creation in Human Resource and Digital Service Systems: A Systematic Literature and Bibliometric Review - Andaru, Rizka Kurnia Andaru; Maulida, Nesya Nandini; Urfina, Yasyifa Dian; Syiam, Nazilatus (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to systematically explore the scholarly development surrounding value co-creation over the past decade. Particular emphasis is placed on understanding the literature's conceptual structure and thematic directions, especially within the framework of service-dominant logic, digital transformation, and the active engagement of actors in value-creation processes. A Systematic Literature Review (SLR) was conducted following the PRISMA protocol, complemented by bibliometric analysis using data sourced from the Scopus database. A total of 75 journal articles published between 2015 and 2025 were examined through the Bibliometrix R package. The analysis reveals a stable growth in academic output, with most contributions originating from the United Kingdom, the United States, and Australia. Key focal points include actor-to-actor engagement, resource integration, the role of artificial intelligence in organizational transformation, and co-production within service ecosystems. The reviewed literature indicates a significant shift from traditional firm-centric perspectives to collaborative, ecosystem-based models involving human and technological actors. These findings offer valuable insights for practitioners and policymakers in designing service strategies grounded in collaboration, fostering digital engagement platforms, and innovating actor-centric business models. Furthermore, the study enhances our understanding of how value is increasingly shaped by stakeholder participation and the mediating role of advanced technologies.